(untitled) (Economic and Political Thought, 2023)
The entry into force of the Law of July 20, 2018: The Law on Higher Education and Science imposed an obligation on universities to assign studies in a given field of study to at least one discipline. When more than one discipline is assigned to a particular field of study, it is necessary to determine the leading discipline within which more than half of the assumed learning outcomes will be obtained by students. This article aims to analyze the legal and factual conditions of this obligation. The legal conditions were analyzed by interpreting the relevant regulations of the law in question and its accompanying implementing act, i.e. the Decree of the Minister of Education and Science of October 11, 2022 on the fields of science and scientific and artistic disciplines. The interpretative position No. 5/2020 of the Presidium of the Polish Accreditation Committee of July 2, 2020 on the assignment of fields of study to scientific or artistic disciplines was also analyzed. The factual conditions were verified on the example of studies in the field of political science using the data contained in the RAD-on ICT system.